Increased speed and image quality in single-shot fast spin echo imaging via variable refocusing flip angles - Andreas M. Loening (2018)
© 2015 Wiley Periodicals, Inc. Purpose To develop and validate clinically a single-shot fast spin echo (SSFSE) sequence utilizing variable flip angle refocusing pulses to shorten acquisition times via reductions in specific absorption rate (SAR) and improve image quality. Materials and Methods A variable refocusing flip angle SSFSE sequence (vrfSSFSE) was designed and implemented, with simulations and volunteer scans performed to determine suitable flip angle modulation parameters. With Institutional Review Board (IRB) approval/informed consent, patients referred for 3T abdominal magnetic resonance imaging (MRI) were scanned with conventional SSFSE and either half-Fourier (n = 25) or full-Fourier vrfSSFSE (n = 50). Two blinded radiologists semiquantitatively scored images on a scale from -2 to 2 for contrast, noise, sharpness, artifacts, cardiac motion-related signal loss, and the ability to evaluate the pancreas and kidneys. Results vrfSSFSE demonstrated significantly increased speed (â142-fold, P < 0.0001). Significant improvements in image quality parameters with full-Fourier vrfSSFSE included increased contrast, sharpness, and visualization of pancreatic and renal structures with higher bandwidth technique (mean scores 0.37, 0.83, 0.62, and 0.31, respectively, P ≤ 0.001), and decreased image noise and improved visualization of renal structures when used with an equal bandwidth technique (mean scores 0.96 and 0.35, respectively, P < 0.001). Increased cardiac motion-related signal loss with full-Fourier vrfSSFSE was seen in the pancreas but not the kidney. Conclusion vrfSSFSE increases speed at 3T over conventional SSFSE via reduced SAR, and when combined with full-Fourier acquisition can improve image quality, although with some increased sensitivity to cardiac motion-related signal loss.